Surgical leadership in Poland: ideas and challenges - Wallner, Grzegorz; Solecki, Michał (Innovative surgical sciences, 2019)
The Polish system of undergraduate and postgraduate medical education, including specialization courses in surgery, provided only general guidelines concerning the issue of creating a leader or preparing for leadership. The process of building the position of a leader has had a rather spontaneous character thus far; it has been based on the individual, natural predispositions of a candidate for the position of a leader. There are no formal guidelines for this in Poland. It is required that graduates of medical studies or residents should acquire the so-called professional and social skills before they complete their specialization training. In the light of the ongoing debate, it seems worthwhile to give a thought on the role of a leader and to undertake harmonized actions to work out a common stance on understanding the issue of leadership and teach leadership skills as a part of a harmonized, methodologically correct system of education, so that the best ways of preparing residents to perform the role of a leader in surgical and other medical surroundings could be realized.